Taman Nasional, Hak-hak Masyarakat Setempat dan Pembangunan Regional - Semiarto Aji Purwanto (Antropologi Indonesia, 2005)
The management of natural resources is authorized with local regulations when dealing with forest community and legal law including some parties from outside of particular forest area. The two contrasts between the local and national regulations have frequently taken place as result of conflict of interest. Therefore some questions arise: how is the development of such conservation areas meet with the local regulation or adat? Is the activity to make use of the resources by the community remains possible? To response to the question the writer would like to argue that assessment of how a national park management interact with local regulations and hak ulayat or communal rights, one should aware of the contexts of their interaction as well as the following aspects: historical, adat law, economical, institutional and the dynamic of local politics. These have to be emphasized since the national park policy in Indonesia can be seen as the manifestation of state territorialization which results in the marginalization of adat community. All parties' interests in natural resources are consider as national citizen and legally authorized to manage or exploit the resources inside the country's territory. Cases from the four national parks observed concluded that even when they live in around the parkas indigenous, they are not automatically awarded their traditional rights or access to make use of the parks. Key words: national park; territorialization; 'masyarakat adat', natural resources management.